2006
DOI: 10.1017/s0952523806231122
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of visual receptive fields in experimental glaucoma

Abstract: Glaucoma is a major cause of blindness and is characterized by death of retinal ganglion cells. In a rat model of glaucoma in which intraocular pressure is raised by cautery of episcleral veins, the somata and dendritic arbors of surviving retinal ganglion cells expand. To assess physiological consequences of this change, we have measured visual receptive-field size in a primary retinal target, the superior colliculus. Using multiunit recording, receptive-field sizes were measured for glaucomatous eyes and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 17 publications
(13 reference statements)
4
31
0
2
Order By: Relevance
“…In primates glaucoma RGC death leads to changes in the lateral geniculate nucleus (LGN) and visual area 1 where cell loss and the shrinkage of lateral geniculate nucleus was noted (23). Similar changes have been shown in the death of specific cell types in the LGN (22,24,28). In spite of massive literature that has emerged in the past decade regarding glaucoma, we are still uncertain regarding the initiation of RGC death.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…In primates glaucoma RGC death leads to changes in the lateral geniculate nucleus (LGN) and visual area 1 where cell loss and the shrinkage of lateral geniculate nucleus was noted (23). Similar changes have been shown in the death of specific cell types in the LGN (22,24,28). In spite of massive literature that has emerged in the past decade regarding glaucoma, we are still uncertain regarding the initiation of RGC death.…”
Section: Introductionmentioning
confidence: 70%
“…Recent evidence from mouse and rat studies showed that the optic axonal terminal synapses degenerate from the distal to proximal direction and precede the degeneration and death of RGCs (33)(34)(35). We theorize that the larger visual receptive fields in the superior colliculus of rats with elevated IOP may be the consequence of expanding terminals of the intact axons into spaces vacated by dying retinal axon terminals (22). Within 6-8 weeks of induced glaucoma, electrophysiological mapping showed no significant changes in receptive field sizes when recorded in the superior colliculus.…”
Section: Evaluation Of Recent Findingsmentioning
confidence: 86%
See 2 more Smart Citations
“…No bead models have been used for invasive electrophysiological assessment of retinal ganglion cells and the only published study is based on an episcleral cautery model (King et al, 2006). It is likely that the majority of microbead models result in some obscuration of the visual axis.…”
Section: Ratmentioning
confidence: 99%